Father Browne's Titanic album : a passenger's photographs and personal memoir - O'Donnell, E. E. (Edward Eugene), 1940- (Messenger Publications, Jesuits of Ireland, 2016)
"Thanks to the gift of a ticket from his uncle, a young Jesuit named Francis Browne traveled on the Titanic during her maiden voyage from Southampton, to Cherbourg to Cork. A keen photographer, Fr Browne took many unique photographs of the ship and her passengers. Invited to remain with the ship as it crossed the Atlantic, Fr Browne was saved from possible disaster by a telegram from his Jesuit superior ordering him to "get off that ship". When the unthinkable happened and the Titanic sank, Fr Browne's photographs appeared on the front pages of newspapers all around the world. For many years the photographs of Fr Browne were forgotten until 1985 when Fr Eddie O'Donnell happened across an old tin trunk in the Jesuit archives and re-discovered 42,000 photographs, including the Titanic collection. The book includes many extracts from Fr Browne's personal Titanic album."--Amazon.com